Solve this problem?
Attachments:
![](https://hi-static.z-dn.net/files/db8/433bafd1d4c058aac3162af6d2c1f1d7.jpg)
Answers
Answered by
1
Hope it is correct and helps u definitely And thanks for asking doubt
Attachments:
![](https://hi-static.z-dn.net/files/de0/c72e3501af2af05f81a71179b1152138.jpg)
Answered by
2
Given equation is (a^2 - 2ab) - (c^2 - 2bc)
= > a^2 - 2ab - c^2 + 2bc
= > a^2 - c^2 - 2ab + 2bc
we know that a^ 2 - b^2 = (a + b)(a - b)
= > (a + c)(a - c) - 2b(a - c)
Take a - c common
= > (a - c)[(a + c) - 2b]
Hope it helps!
= > a^2 - 2ab - c^2 + 2bc
= > a^2 - c^2 - 2ab + 2bc
we know that a^ 2 - b^2 = (a + b)(a - b)
= > (a + c)(a - c) - 2b(a - c)
Take a - c common
= > (a - c)[(a + c) - 2b]
Hope it helps!
Similar questions